The Effect of Limb Muscle Explosive Power Training on the Speed of the Results of Pencak Silat Kicks of PSHT Students - Fuorteino, Junerensa; Kristina, Putri Cicilia; Hermansah, Bambang (Journal of Social Work and Science Education, 2023)
Internal problem study this is there any effect of leg muscle explosive power training on the speed of sickle kick results of Pencak Silat PSHT students at SMA Negeri 4 Sekayu. The purpose of this study was to determine whether or not there was an effect of leg muscle explosive power training on the speed of sickle kick results of Pencak Silat PSHT Students of SMA Negeri 4 Sekayu. The method used in this study uses the method Experiment Design That is pre- Experiment Design Often also called “Almost Experiment” or mock experiments. The type of design used one group pretest-posttest design. Data collection techniques with tests. Data analysis techniques using statistical analysis. Researchers use several method statistics, namely simple linear regression, product moment correlation, and testing the hypothesis used t test The conclusion shows the results of the regression Y = 0.008 + 1.16 X the results of calculating the product moment correlation (rxy) of 0.17 is included in the category of the level of a strong relationship between the independent variables and the variables bound, and the determinant coefficient (r2) = 51% of the speed of sickle kick results and the rest is influenced by other factors. Also, through hypothesis testing, namely t-count> t-table (5.29 > 1.701). clarifies that Ha is accepted and Ho rejected significantly. Thus, there is an effect of muscle explosive power training limbs on the speed of the sickle kick results of Pencak Silat PSHT students at SMA Negeri 4 Sekayu.